PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SD ISLAM SURYA BUANA MALANG - Hasna Nur Isnaini; Nur Hidayati; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to analyze the effect of work motivation, work environment and work discipline on teacher performance at SD Islam Surya Buana Malang.The population and sample in this study were all teachers of SD Islam Surya Buana Malang, totaling 30 people. Data collection using a questionnaire, with multiple linear regression analysis method.            The results showed that work motivation, work environment and work discipline simultaneously affect the performance of teachers at SD Islam Surya Buana Malang. Work motivation and work discipline significant effect the performance of teachers at SD Islam Surya Buana Malang. Meanwhile, the work environment has no significant effect on the performance of teachers at SD Islam Surya Buana Malang. Keywords: Teacher Performance, Work Motivation, Work Environment, Work Discipline